Effects of a7nAChR agonist on the tissue estrogen receptor expression of castrated rats - Ma, Feng (Int J Clin Exp Pathol, 2015)
Osteoporosis is one common disease in postmenopausal women due to depressed estrogen level. It has been known that inflammatory factors are involved in osteoporosis pathogenesis. One regulator of inflammatory cascade reaction, a7-nicotinic acetylcholine receptor (a7nAChR), therefore, may exert certain role in osteoporosis. This study thus investigated this question on an osteoporosis rat model after castration. Rats were firstly castrated to induce osteoporosis, and then received a7nAChR agonist (PNU-282987), diethylstilbestrol or saline via intraperitoneal injection. After 6 or 12 weeks, bone samples were collected for counting osteoblast number, bone density and estrogen receptor (ERα and ERβ) expression, in addition to the serum laboratory of inflammatory factors. Bone density, osteoclast number, ERα and ERβ expression level were significantly depressed in model group, and were remarkable potentiated in the drug treatment group (P<0.05). The levels of BGP and PTH in drug treatment group were decreased compared to diethylstilbestrol group, while E2 and IGF-1 showed up-regulation. Agonist of a7nAChR can up-regulate estrogen receptor expression and may prevent the occurrence and development of osteoporosis.